Which equation is equivalent to 3[7x - 4(x - 3)] + 1 = 16?

A.) 9x - 2 = 16

B.) 9x + 37 = 16

C.) 17x - 2 = 16

D.) 17x + 13 = 16

A.) 9x - 2 = 16

B.) 9x + 37 = 16

C.) 17x - 2 = 16

D.) 17x + 13 = 16

3[7x - 4(x - 3)] + 1 = 16

3(7x - 4x + 12) + 1 = 16 {used distributive property with -4}

3(3x + 12) + 1 = 16 {combined like terms}

9x + 36 + 1 = 16 {used distributive property with 3}

9x + 37 = 16 {combined like terms}

3(7x - 4x + 12) + 1 = 16 {used distributive property with -4}

3(3x + 12) + 1 = 16 {combined like terms}

9x + 36 + 1 = 16 {used distributive property with 3}

9x + 37 = 16 {combined like terms}

**B.) 9x + 37 = 16***Ask Algebra House*